2022
DOI: 10.1111/hel.12923
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of oral microbiota alterations induced by Helicobacter pylori infection and vonoprazan‐amoxicillin dual therapy for Helicobacter pylori eradication

Abstract: Background The oral cavity is considered a potential reservoir of Helicobacter pylori (H. pylori), and the imbalance of oral microbiota directly reflects the health of the host. We aimed to explore the relationship among oral microbiota, H. pylori infection, and vonoprazan‐amoxicillin (VA) dual therapy for H. pylori eradication. Methods Helicobacter pylori‐positive patients were randomized into low‐ or high‐dose VA dual therapy (i.e., amoxicillin 1 g b.i.d. or t.i.d. and vonoprazan 20 mg b.i.d) for 7 or 10 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 34 publications
(84 reference statements)
3
39
1
Order By: Relevance
“…Recently, several randomized controlled trials (RCTs) [18][19][20][21][22][23] regarding VA dual therapy versus BQT for H. pylori eradication have been published in 2023, but the results were inconsistent and controversial. Hence, we performed a systematic review and meta-analysis of RCTs to compare the effects of VA dual therapy with BQT for H. pylori eradication.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several randomized controlled trials (RCTs) [18][19][20][21][22][23] regarding VA dual therapy versus BQT for H. pylori eradication have been published in 2023, but the results were inconsistent and controversial. Hence, we performed a systematic review and meta-analysis of RCTs to compare the effects of VA dual therapy with BQT for H. pylori eradication.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy was improved (>90%) when the treatment duration was extended to 14 days. [25][26][27][28][29][30] It should be note that all the VA groups were treated with VPZ 20 mg bid and we found that high dose and low dose amoxicillin does not contribute significant difference to the cure rate. Possibly, a universally effective regimen will emerge, but it will likely require higher doses of VPZ such as 30 or 40 mg bid or tid in some regions.…”
Section: F I G U R Ementioning
confidence: 56%
“…As for the comparison between VA dual therapy and bismuth-containing quadruple therapy, no significant difference was observed as well. 12,25,26,28 The adverse events rate of VA dual therapy was lower than VPZ triple therapy and bismuth-containing quadruple therapy, which In contrast to the four previous systematic reviews and meta-analysis, 8,[35][36][37] our study incorporates nine articles. 12,[24][25][26][27][28]34,38 Compared with previous meta-analysis, we made a comprehensive analysis to compare the efficacy and safety of VA dual ther- This meta-analysis had several limitations that should be considered.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic resistance was considered when MIC ≥1 μg/mL for clarithromycin; ≥2 μg/mL for levofloxacin, amoxicillin, tetracycline, and furazolidone; and ≥8 μg/mL for metronidazole. [17][18][19] Outcomes. The presence of H. pylori was re-assessed using a 13 C-UBT (Beijing Richen-Force Science & Technology Co. Ltd.) after 6 weeks following completion of the treatment.…”
Section: Methodsmentioning
confidence: 99%